2016
DOI: 10.17576/mjas-2016-2003-24
|View full text |Cite
|
Sign up to set email alerts
|

CONDUCTIVITY AND THERMAL STABILITY OF SOLID ACID COMPOSITES CsH2PO4/NaH2PO4/SiO2

Abstract: Solid acid composites CsH 2 PO 4 /NaH 2 PO 4 /SiO 2 with different mole ratios of CsH 2 PO 4 and NaH 2 PO 4 to SiO 2 were synthesized and characterized. Preliminary infrared measurements of CsH 2 PO 4 and its composites indicated that hydrogen bonds breaking and formation were detected between 1710 to 2710 cm -1 , while the rotation of phosphate tetrahedral anions occurred between 900 and 1200 cm -1 . The superprotonic transition of CsH 2 PO 4 /NaH 2 PO 4 /SiO 2 composite was identified at superprotonic temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…We also found that the conductivity of solid acid composites at a high temperature slightly increases due to the hydrophobicity and surface area of ZrO 2 . 40 The conductivity of CDP/SDP/ZrO 2 increased to 1.5 orders of magnitude in the LT region and high temperature which was due to the structural disorder and deformation of the cation shape of ZrO 2 . 31 Furthermore, we investigated the time dependence of the ionic conductivity of CDP, SDP, and 8CDP/1SDP/1ZrO 2 under high hermetically confined conditions.…”
Section: Materials Advances Papermentioning
confidence: 94%
“…We also found that the conductivity of solid acid composites at a high temperature slightly increases due to the hydrophobicity and surface area of ZrO 2 . 40 The conductivity of CDP/SDP/ZrO 2 increased to 1.5 orders of magnitude in the LT region and high temperature which was due to the structural disorder and deformation of the cation shape of ZrO 2 . 31 Furthermore, we investigated the time dependence of the ionic conductivity of CDP, SDP, and 8CDP/1SDP/1ZrO 2 under high hermetically confined conditions.…”
Section: Materials Advances Papermentioning
confidence: 94%
“…In addition, comprehensive studies of composite systems based on a number of acidic salts of Me x H y (AO 4 )z: MeHSO 4 (Me = Cs, Rb, K), Cs 5 H 3 (SO 4 ) 4 , (NH 4 ) 3 H(SO 4 ) 2 , CsH 2 PO 4 , and silicon dioxide with a different specific surface area (10. . .580 m 2 /g) were carried out [44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%